PEMBUATAN Carboxymethyl cellulose (CMC) DARI PELEPAH NANAS (Ananas cosmosus Merr.) - Ripdayana Ripdayana; Ahmad Ridhay; Erwin Abdul Rahim (KOVALEN: Jurnal Riset Kimia, 2019)
A research about production of Carboxymethyl cellulose (CMC) from pineapple midrib (Ananas cosmosus Merr.) has been conducted. This research aims to determine the best cellulose ratio with sodium monochloro acetate and the best reaction time to the substitution degree of carboxymethyl cellulose from pineapple midrib fibers. This study used a Completely Randomized Design method with two independent variables, i.e. variations in the weight of sodium monochloroacetate (2.5 grams, 3 grams, 3.5 grams, 4 grams, and 4.5 grams) and variations in reaction time (1 hour, 2 hours, 3 hours, 4 hours , and 5 hours), each treatment was done duplo using 20 treatment units. The result of the study showed that the best ratio of sodium monochloroacetate to cellulose which produced carboxymethyl cellulose from pineapple midribs was 2.5: 2.5 with substitution degree value of 1.93 and optimum reaction time which produced carboxymethyl cellulose from pineapple midribs was 1 hour with substitution degree of 2.38. Keywords: Carboxymethyl cellulose, Pineapple midrib